Executive Committee Minutes 2014-02-27 - Academic Senate:::::::::
Minutes of 1/30/14 – Approved. Agenda – Approved. Chair Report. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. Request to add At-Large members to UPRS. EPC Report. FSAC Report. Associated Students Report. Senate agenda approved.